(untitled) (Acta Scientiarum. Agronomy, 2022)
In soils with adequate levels of fertility, it is possible to manage phosphate fertilization aiming at the grain production system, instead of each isolated crop. The objective was to evaluate the effects of the management of phosphate fertilization, place and time, on the soil and leaf P content, and crop yield in grain production systems. An experiment was conducted at the farm level in the municipality of Nazareno, state of Minas Gerais, Brazil, for four years on soil with adequate level of fertility. The treatments consisted of the management of phosphate fertilization by broadcast or furrow and dose for each crop or for the production system (spring/summer and autumn/winter crops), being: Control = without phosphate fertilization; Conventional = phosphate fertilization in the furrow in each crop; BTP = phosphate fertilization of the grain production system to broadcast; TPS = phosphate fertilization of the grain production system in the furrow of the spring/summer crop; TPW = phosphate fertilization of the grain production system in the furrow of the autumn/winter crop. Soil P content was evaluated in the third year of implantation, and the crops yield every season crop (maize, soybean, common bean and wheat). The P content in the leaves of maize and soybeans were evaluated in the spring/summer crops. The application of the total dose of phosphate fertilization for both crops in the sowing furrow of the spring/summer or autumn/winter crops (TPS and TPW) promoted operational advantages and increased soil P content in the 0-0.20 m layer, without reducing the yield of the spring/summer crops. Leaf P content was not affected. The Conventional management (phosphate fertilization in the furrow in each crop) provide greater yield of common beans and wheat during autumn/winter crops, which are more subject to water restriction due to less rainfall, even without increasing the soil P content.